PENGUATAN NILAI-NILAI GOTONG ROYONG MELALUI TRADISI CABUT BAWANG DALAM MENINGKATKAN KESEJAHTERAAN DAN KEHARMONISAN MASYARAKAT DI DESA TINDALUN, KEC. ANGGERAJA, KAB. ENREKANG. - M. Iqbal. K; Adelia Hanafiyah Samhah; Fadillah Mubakkirah; Hildayani Hildayani (IAI DDI Mangkoso, 2023)
Indonesia is a pluralistic country with many differences, ranging from ethnicity, race, religion, language, beliefs and customs. This requires values to unite and advance Indonesian society. One of the values that can unite is the value of gotong royong, but the value of Gotong royong has been eroded by the times. This is what makes researchers make this journal with the aim of knowing the strengthening of mutual cooperation values through the onion pulling tradition in improving the welfare and harmony of the Tindalun village community, Anggeraja sub-district, Enrekang district. This type of research uses qualitative research with a descriptive approach. The object of this research is to find out how the community views Gotong royong, whether the tradition of gotong royong cabut bawang has a social impact and economic impact on the community. And how empowerment is done to maintain the tradition of pulling onions. The subjects of this research are sourced from the community, onion farmers, community leaders, and youth leaders. With data collection techniques from observation and interviews. The results of this study show that mutual cooperation can build friendship, work together, and strengthen togetherness. From this onion pulling gotong royong also has social impacts such as, the love of deliberation, building awareness and strengthening friendship. While the economic impact is minimising.